2003
DOI: 10.3233/jad-2003-5103
|View full text |Cite
|
Sign up to set email alerts
|

Aggresome formation by mutant prion proteins: The unfolding role of proteasomes in familial prion disorders

Abstract: Although familial prion disorders are a direct consequence of mutations in the prion protein gene, the underlying mechanisms leading to neurodegeneration remain unclear. Potential pathogenic mechanisms include abnormal cellular metabolism of the mutant prion protein (PrP M ), or destabilization of PrP M structure inducing a change in its conformation to the pathogenic PrP-scrapie (PrP Sc ) form. To further clarify these mechanisms, we investigated the biogenesis of mutant PrP V203I and E211Q associated with Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 18 publications
2
39
1
Order By: Relevance
“…PrP-containing aggresomes have been observed in cells expressing mutant PrP (Singh et al, 2005) or with enforced expression of wild-type PrP directly to the cytosol (Goggin et al, 2008), and in cells expressing tagged and/or mutated, mature PrP from a strong promoter and treated with epoxomicin, ALLN or CsA (Ma & Lindquist, 2001;Cohen & Taraboulos, 2003;Mishra et al, 2003). However, no aggresome formation appears to occur following proteasome inhibition in cells that express wild-type, endogenous PrP (Kristiansen et al, 2005 and this study).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…PrP-containing aggresomes have been observed in cells expressing mutant PrP (Singh et al, 2005) or with enforced expression of wild-type PrP directly to the cytosol (Goggin et al, 2008), and in cells expressing tagged and/or mutated, mature PrP from a strong promoter and treated with epoxomicin, ALLN or CsA (Ma & Lindquist, 2001;Cohen & Taraboulos, 2003;Mishra et al, 2003). However, no aggresome formation appears to occur following proteasome inhibition in cells that express wild-type, endogenous PrP (Kristiansen et al, 2005 and this study).…”
Section: Discussionmentioning
confidence: 96%
“…A further question is whether the abnormal PrP 26K species that is produced in proteasome-impaired cells and exhibits unusual biochemical characteristics reminiscent of PrP Sc hallmarks might contribute to PrP Sc formation in TSE diseases, as proposed by some authors (Yedidia et al, 2001;Mishra et al, 2003). Whilst proteasome inhibition led to accumulation to similar levels of unglycosylated -possibly retrotranslocated -PrP species in infected and uninfected CAD cells, we failed to detect any difference in the PrP Sc glycoform profiles of the untreated and treated cultures, even when cells were cultivated with proteasome inhibitors for several days.…”
Section: Discussionmentioning
confidence: 99%
“…For V180I, V210 and F198S PrP, it was found that a folding intermediate increased in the population relative to the native fold, further indicating that these mutations cause instability [89,151]. Studies of V203I PrP are limited, but may suggest an effect on stability as well [152]. For T183A, the observed instability may be related to the loss of the hydrogen bond between Thr183 (in HB) and Y162 (in S2).…”
Section: Mutations In the Hydrophobic Corementioning
confidence: 99%
“…Interestingly, PS1 molecules that harbor other fAD-causing mutations accumulate within the ER upon proteasome inhibition (Ben-Gedalya et al 2015), showing that distinct conformers of the same protein can be sorted to distinct cellular deposition sites. Toxic PrP species (Kristiansen et al 2005), disease-causing PrP mutants (Cohen and Taraboulos 2003;Mishra et al 2003), and PD-associated, aggregated a-synuclein (Tanaka et al 2004;Wong et al 2008) were also shown to be deposited in aggresomes of mammalian cells, further linking these sites with human illnesses. However, the question of whether the accumulation of aggregated proteins in an aggresome is protective or deleterious to the cell remains largely unanswered.…”
Section: Cellular Deposition Sitesmentioning
confidence: 99%